Research on Differences in Knowledge Demand of Sustainability Learning of Teams in Mega Engineering Construction Project in China - Jinfan Zhang; Yun Chen; Wenxi Zhu; Jianrong Cai (Advances in Civil Engineering)
Knowledge plays a vital role in achieving sustainable development goals (SDGs) in construction industry. According to the view of organization learning, heterogeneous teams have heterogeneous core knowledge. The main aim of this study is to explore the differences in demand for sustainability learning knowledge (SLK) among the mega engineering construction project (MECP) teams, which has important implications for improving the performance of team learning and achieving SDGs in MECPs. This study followed a research design that included identifying SLK and the stakeholder teams that needed SLK and investigating the respondents’ perception of the level of demands for SLK through semistructured interviews and survey questionnaires executed in China. The statistical test results indicated that there were some significant differences in demands for some SLK among the MECP teams and MECPs. All types of MECP teams had a common high demand for SLK on environment, safety, and health in China. This study contributes to research on sustainable construction in MECPs in two main ways: (1) it reveals novel insights related to the integration of SL into the MECPs sustainable construction practices for developing countries and (2) it offers the possibility for practitioners to identify the most crucial knowledge and focus their efforts and resources efficiently.